Characteristics of sub-tidal coastal trapped disturbances in sea level along the coasts of Namibia and South Africa - De Cuevas, Beverly Ann (Department of Oceanography, 2024)
[Page i missing] The sea level disturbances are found not to be free waves but forced waves needing constant forcing in order to propagate. Along the east coast where such forcing is absent, particularly in summer, there is no general propagation. If the forcing extends further eastwards, as sometimes occurs during winter, this is reflected in the sea level response.